1995
DOI: 10.1093/infdis/172.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Impairs Macrophage Defense against Mycobacterium avium Complex

Abstract: Pentoxifylline, a tumor necrosis factor-alpha (TNF) inhibitor, is being tested as a treatment adjunct in human immunodeficiency virus (HIV)-infected patients. However, TNF is important in cellular defense. The effect of pentoxifylline on Mycobacterium avium complex (MAC) growth in exogenously infected macrophages was compared with the effect of dexamethasone. Pentoxifylline, in a concentration that decreased MAC-induced TNF by 48.1%, enhanced MAC growth by 1.9- to 19.6-fold and 1.82- to 4.46-fold in macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…PTX may prevent the progressive renal fibrosis by reducing the upregulation of these growth factor and collagen genes in the remnant kidney, which is the third possible mechanism for its renoprotective effect. However, the inhibition of TGF-␤ 1 signaling and suppression of cellular immunity by PTX may impair the mechanisms for defense and healing in surgical wound (44). This may probably explain why we observed poor healing of surgical wound and higher mortality in rats receiving PTX from the day of surgery in the pilot study.…”
Section: Discussionmentioning
confidence: 84%
“…PTX may prevent the progressive renal fibrosis by reducing the upregulation of these growth factor and collagen genes in the remnant kidney, which is the third possible mechanism for its renoprotective effect. However, the inhibition of TGF-␤ 1 signaling and suppression of cellular immunity by PTX may impair the mechanisms for defense and healing in surgical wound (44). This may probably explain why we observed poor healing of surgical wound and higher mortality in rats receiving PTX from the day of surgery in the pilot study.…”
Section: Discussionmentioning
confidence: 84%
“…Treatment of M. avium-infected SCID and BALB/c mice with anti-TNF-␣ antibody was shown to increase mycobacterial CFU in the spleens and livers (1,8) and reduce the protective effect of immunization with BCG (1). Antibody to TNF-␣ inhibited in vitro killing of MAC in human monocyte-derived macrophages activated with vitamin D (5), and treatment of ex vivo-or in vitro-infected human monocyte-derived macrophages with pentoxifylline or dexamethasone enhanced MAC growth (31,32). Similarly, treatment of MAC-infected murine peritoneal macrophages with pentoxifylline or anti-TNF-␣ antibody suppressed the anti-mycobacterial response induced by activation of the macrophages with IFN-␥ and TNF-␣ (16).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-3, IL-6, and macrophage colony-stimulating factor have been reported to increase mycobacterial burden in vitro (34). It is of interest to note that dexamethasone and pentoxifylline showed opposite effects on IL-6 production; dexamethasone was shown to suppress IL-6 production, whereas pentoxifylline enhanced it (31). The relevance of these findings to in vivo situations is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We doubt that MAC itself is the cause of distal symmetric polyneuropathy given most of our patients (seven of 13) did not have overt MAC infections as was the case with five of 17 definite cases of distal symmetric polyneuropathy in the study by Norton et al . We also considered the possible role of isoniazid, although only three of our patients had taken isoniazid in the past, and concluded that cytokines such as tumour necrosis factor and interleukin-6, known to be raised in MAC infections,4 5 may be involved.…”
mentioning
confidence: 99%